Novel Agonists of the Juvenile Hormone Signaling - Miláček, Matěj (Jihočeská univerzita, 2021)
Juvenile hormone (JH) plays a key role in insect development. In larval stage, JH prevents the insect to metamorphose. While JH is unique to arthropods and absent from vertebrates, it represents potential tool for insect control. Combination of cell-based assay and high-throughput screening enabled to find candidate JH agonists (JHags) that activate JH signaling via juvenile hormone receptor (JHR). This thesis aims to elucidate the effect of these JHags on three evolutionary distinct insect species in vivo and possible selectivity of the JHags for individual insect species in vitro. In addition, we provide evidence that JHR from hemimetabolous species Blattella germanica and Prorhinotermes simplex binds JH in vitro. This thesis provides useful findings and tools for development of new JHags that could be selective for particular insect taxa.
Novel Agonists of the Juvenile Hormone Signaling